Risk Prevention of Data Leakage by Commercial Banks - Biolcheva, Petia (Research Papers, 2016)
Information is one of the key assets of commercial banks. The loss of bank information in question might be in serious financial and reputational damage to the bank. In the recent years, criminal activities related to bank robberies are occurring increasingly bringing new risks of the criminogenic kind. Primary position among them occupy cybercrime connected to drawing off bank information. This study is aimed at revealing the theoretical and empirical aspects of prevention and control of the risk of data leaks. It is developed methodical scheme for prevention of that risk. Identified are channels of data leaks and their character. The paper is illustrated with an empirical study on a sample of commercial banks, which has been studied the manifestation of the risk of leaks. Below are the defense mechanisms and most often risk situations that threaten the banking information security. Contoured is the trend in respect to the risks of major internal and external sources of threat.